A review on anticipatory grief: a lessons learnt from the history of Abu Bakr r.a. - Md Rosli, Najwa Hanim; Md Tahir, Mohd Faiz; Harris, Jefri Irwan; Sakhi Mohd, Muhammad Al Siddiq; Nasution, Nor Jannah; Razali, Zul Azlin (2016)
Introduction: Grief is defined as ‘the internal experience of a person to the loss of something loved and valued’. It is a normal and expected reaction to loss. While anticipatory grief is defined as ‘an emotional response that is experienced before a true loss’, a concept focusing on that a person might experience grief when the loss of a close loved one was anticipated, but had not yet occurred. Description from history: The history of Abu Bakr r.a. was reviewed especially from the period of a few months before and recently after the death of the prophet s.a.w. It was noted that he appeared strong while others were down grieving upon the news of the prophet s.a.w.’s death. It was also noted that Abu Bakr r.a. has been grieving when he anticipated that the prophet was going to die. Discussion: Literatures on anticipatory grief were reviewed. Evidence are conflicting on the role of anticipatory grief. Factors that lead to these differences will be reviewed. And the factors in Abu Bakr r.a. that helped maintain his composure after the death of prophet Muhammad s.a.w. and later led him to be the pledged as the first caliph of the Muslim nation will be discussed.